The role of Linguistics and stylistics in Modern English - Nazokat Khazratqulova Farhadjon kizi (Periodica Journal, 2024)
This article delves into the significant roles played by linguistics and stylistics in the context of Modern English. By examining the interplay between language structure, usage, and literary expression, it explores how these disciplines contribute to our understanding and appreciation of the English language in contemporary settings.
Keywords: Linguistics; stylistics; modern english; language